The narrow road to the deep north eaudiobook - Flanagan, Richard (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2014)
From the winner of Australia's National Fiction Prize, author of the hugely acclaimed Gould's Book of Fish, comes a magisterial, Rashomon-like novel of love and war that traces the life of one man from World War II to the present. In the despair of a Japanese POW camp on the Thailand–Burma Death Railway in 1943, Australian surgeon Dorrigo Evans is haunted by his love affair with his uncle's young wife two years earlier. His life is a daily struggle to save the men under his command from starvation, from cholera, from pitiless beatings—until he receives a letter that will change him forever. Moving deftly from the POW camp to contemporary Australia, from the experiences of Dorrigo and his comrades to those of the Japanese guards, this savagely beautiful novel tells a story of death, love, and family, exploring the many forms of good and evil, war and truth, guilt and transcendence, as one man comes of age and prospers, only to discover all that he has lost.